2013
DOI: 10.1017/s0022377813000470
|View full text |Cite
|
Sign up to set email alerts
|

Post-pinch generation of electron beam in a low energy Mather-type plasma focus device

Abstract: The post-pinch generation of electron beam in a low energy Mather-type plasma focus (PF) device has been investigated. A fast-calibrated Rogowski coil was used to monitor the emission of electron beam. A two-channel diode X-ray spectrometer along with suitable filters provided the records of energy spectrum of X-ray radiation. Single time-period emissions of electron beam with duration of 100 to 20 ns were recorded in the high range of the device operating pressure (0.8-2 mbar). However, in the low range regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The analyses have shown that plasma resistance may reach 0.2 Ω during the phase with anomalous resistances and the minimum anode voltage to generate hard X-rays in this phase is about 13 kV [12]. Single and multiple peaks of an electron beam that are highly correlated with the radiated X-rays and anode voltage have been studied [13].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The analyses have shown that plasma resistance may reach 0.2 Ω during the phase with anomalous resistances and the minimum anode voltage to generate hard X-rays in this phase is about 13 kV [12]. Single and multiple peaks of an electron beam that are highly correlated with the radiated X-rays and anode voltage have been studied [13].…”
mentioning
confidence: 99%
“…A high-voltage probe with a rise time of about 2 ns is used to measure the anode voltage. The working gas is argon [9][10][11][12][13]. The solid anode is 2 cm in diameter with a flat top of 1 cm in diameter at the center and a rounded edge.…”
mentioning
confidence: 99%
“…The capacitance was 10 lF and the static inductance of 150 nH. [10][11][12][13] The radius of central electrode (anode) was 1 cm and the ratio of the radius of cathode to the radius of anode was 3. A Tektronix P6015A high voltage probe was used to monitor the tube voltage.…”
mentioning
confidence: 99%
“…A photomultiplier tube (PMT) in conjunction with a suitable plastic scintillator, a four-channel diode X-ray spectrometer (DXS), a faraday cup, and a fast Rogowski coil have been used to measure the x-ray radiation and charged particle beams emissions from the device. [10][11][12][13] All signals were transmitted by a three-meter long 50 X coaxial cables with equal-length and recorded by a four-channel, 100 MHz, 1 GSP digital Tektronix oscilloscope.…”
mentioning
confidence: 99%
See 1 more Smart Citation